2015
DOI: 10.1177/0148607114567900
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin E in New‐Generation Lipid Emulsions Protects Against Parenteral Nutrition–Associated Liver Disease in Parenteral Nutrition–Fed Preterm Pigs

Abstract: Introduction Parenteral nutrition (PN) in preterm infants leads to PN-associated liver disease (PNALD). PNALD has been linked to serum accumulation of phytosterols that are abundant in plant oil but absent in fish oil emulsions. Hypothesis Whether modifying the phytosterol and vitamin E composition of soy and fish oil lipid emulsions affects development of PNALD in preterm pigs. Methods We measured markers of PNALD in preterm pigs that received 14 days of PN that included 1 of the following: (1) Intralipid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
100
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 74 publications
(109 citation statements)
references
References 50 publications
7
100
2
Order By: Relevance
“…The vitamin E concentration in IL was insufficient to maintain plasma levels similar to that seen in piglets on the ENT diet. In accordance with our previous study (32), the IL group had a considerable hepatic concentration of -tocopherol, whereas -tocopherol was not detectable in the liver of other groups, or in plasma. The contribution of -tocopherol and the stereoisomer composition of -tocopherol in plasma and liver tissue in the IL versus OV and SL probably reflected the difference in the chemical forms of vitamin E in the emulsions.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The vitamin E concentration in IL was insufficient to maintain plasma levels similar to that seen in piglets on the ENT diet. In accordance with our previous study (32), the IL group had a considerable hepatic concentration of -tocopherol, whereas -tocopherol was not detectable in the liver of other groups, or in plasma. The contribution of -tocopherol and the stereoisomer composition of -tocopherol in plasma and liver tissue in the IL versus OV and SL probably reflected the difference in the chemical forms of vitamin E in the emulsions.…”
Section: Discussionsupporting
confidence: 92%
“…The concentration of -tocopherol per mole percent total unsaturated fatty acids was three times higher in OV and 2.3 times higher in SL compared with IL. At the same lipid dose of 5 g/(kg·d), we recently showed prevention of cholestasis in preterm piglets by supplementing IL with vitamin E to a concentration equivalent to that present in OV (32). However, a recent publication in term piglets administered IL supplemented with vitamin E at 10 g/(kg·d) failed to show any effect on treatment (50).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…33 The authors suggested that other lipid components present in SMOF-based and FO-based ILE, such as vitamin E or ω-3 PUFA, may be protective against PNALD. 33, 34 In subsequent experiments, the, addition of α-tocopherol to SO-ILE prevented the increase in serum and hepatic markers of PNALD, as compared with PN solution containing SO-ILE alone. 34 Furthermore, addition of phytosterols to 100% FO-ILE did not reproduce evidence of PNALD.…”
Section: Pathogenesis Of Ifaldmentioning
confidence: 89%
“…In vitro, fish oil suppresses the lipopolysaccharide-induced inflammatory response in cultured monocytes as well as TGF-b1-induced epithelial-to-mesenchymal transition that characterizes fibrosis in cultured liver epithelial cells (87). A recent study in PN-administered preterm pigs showed that adding 251 mg/L a-tocopherol to a parenterally administered soybean oil lipid emulsion attenuates soybean oil-mediated biochemical evidence of liver injury and reduction in bile acid clearance, thus suggesting a hepatoprotective role for antioxidants in fish oil emulsions (88). Similar to our understanding of parenteral soybean oil hepatotoxicity, our understanding of parenteral fish oil hepatoprotection in the setting of PNALD remains incomplete but is likely multifactorial.…”
Section: Fat Emulsions Used In Pnmentioning
confidence: 99%